2017
DOI: 10.3384/ecp17144187
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Hydraulics for Micro Excavator

Abstract: Environmental restrictions and economic opportunities create demand to investigate the potential of further hybridization of non-road mobile machinery (NRMM). Many proposals for energy saving in hydraulic systems have been researched. In addition to well-established methods, there are zonal or decentralized hydraulics -an approach first introduced in the aircraft industry. In a fully decentralized system, the hydraulic pumps are disconnected from the engine and replaced with hydraulic power packs distributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Minav et al [16] investigated using a hydraulic ERS on a hydraulically operated forklift and reported an energy-saving efficiency of 45%. Zhang et al [23] investigated a direct drive system based on a decentralized hydraulics concept. Two fixed displacement pump/motors with a coaxial installed speed-controlled electric servo motor directly controlled the amount of fluid pumped into and out from the corresponding boom cylinder.…”
Section: Hydraulic Erssmentioning
confidence: 99%
“…Minav et al [16] investigated using a hydraulic ERS on a hydraulically operated forklift and reported an energy-saving efficiency of 45%. Zhang et al [23] investigated a direct drive system based on a decentralized hydraulics concept. Two fixed displacement pump/motors with a coaxial installed speed-controlled electric servo motor directly controlled the amount of fluid pumped into and out from the corresponding boom cylinder.…”
Section: Hydraulic Erssmentioning
confidence: 99%
“…A structural analysis furthermore showed that the original boom structure is safe. In [76] lifting efficiencies ranging from 67% to 77% are simulated for the same excavator.…”
Section: Class B-variable-speed Single Prime Mover With Multiple Pumpsmentioning
confidence: 99%
“…The hose model was updated with a pressure drop. The overall model is considered to be reliable, as it was validated in early studies in [16]; and in addition, the cylinder friction was validated with a micro-excavator [30].…”
Section: Modellingmentioning
confidence: 99%